Exosomal Vimentin from Adipocyte Progenitors Protects Fibroblasts against Osmotic Stress and Inhibits Apoptosis to Enhance Wound Healing - Parvanian Sepideh; Zha Hualian; Su Dandan; Xi Lifang; Jiu Yaming; Chen Hongbo; Eriksson John E.; Cheng Fang (MDPI, 2025)
Mechanical stress following injury regulates the quality and speed of wound healing. Improper mechanotransduction can lead to impaired wound healing and scar formation. Vimentin intermediate filaments control fibroblasts' response to mechanical stress and lack of vimentin makes cells significantly vulnerable to environmental stress. We previously reported the involvement of exosomal vimentin in mediating wound healing. Here we performed in vitro and in vivo experiments to explore the effect of wide-type and vimentin knockout exosomes in accelerating wound healing under osmotic stress condition. Our results showed that osmotic stress increases the size and enhances the release of exosomes. Furthermore, our findings revealed that exosomal vimentin enhances wound healing by protecting fibroblasts against osmotic stress and inhibiting stress-induced apoptosis. These data suggest that exosomes could be considered either as a stress modifier to restore the osmotic balance or as a conveyer of stress to induce osmotic stress-driven conditions.